Post Tsunami Land Use Monitoring to Support Sustainable Coastal Management - Utami, Westi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Monitoring of land use in tsunami prone coastal areas has an important role in disaster risk reduction efforts. This study was conducted to map temporal land use patterns in the post-2004 tsunami Aceh coastal area. The research method was carried out qualitatively, the data were analyzed spatially, by interpreting multitemporal Landsat TM 5 and Landsat 8 imagery to determine patterns and changes in land use. Interpretation and analysis of land use are carried out with supervised classification through the maximum likelihood approach. The results showed that land use patterns in tsunami prone areas, namely around the coast, were still widely used as residential areas. This study shows that over the past 15 years there has been an increase in the number of settlements covering an area of ​​7418.9796 hectares, and there has been a decrease in open land covering an area of ​​6743.73 hectares. While land use in the form of high density vegetation experienced an increase of 672.76 Ha, likewise low density vegetation increased by 459.11 Ha after the tsunami. The growth of settlements in a fairly dense tsunami-prone area can have implications for the high impact / risk if a similar disaster occurs again. Efforts to regulate, monitor, control and evaluate land use appropriately in tsunami prone areas are necessary so that the level of disaster risk can be reduced.